The journey towards social exclusion in Colombia (2010)
There has been continuing forced displacement over many years in the south of the Department of Valle del Cauca in Colombia. Families fleeing conflict and violence between insurgents and government forces have moved into the municipality of Florida which has a population of approximately 55,000. Having lost the economic, social, cultural and symbolic capital accumulated in their home areas, they struggle to compensate for these losses and to preserve or improve on their well-being and living conditions.